STUDY OF FLAME RESISTANCE FOR ADDITIVES – CONTAINING EPOXY AND POLYESTER - Mokhilif, Mohammed Hallol (University of Thi-Qar Journal, 2019)
In this paper, additives dechlorane plus which used synergistically with sodium-orthophosphate and with alumina, sodium-orthophosphate , and alumina have been used as a flame retardants for unsaturated polyester and epoxy resin .The additives were used at low and high levels with unsaturated polyester and they were used at high levels with epoxy resin .At low levels ,the additives were used in weight percentages of (1,3,5,7and 10)%,At high levels ,They were used in weight percentages of (15,20,25,30 and 35 )%.Hand –lay up was used to prepare the specimens .The paper showed that the additives have good effectiveness in reducing the burning at high weight percentages and they appeared high effectiveness in resisting the flame when they were used as a synergistic flame retardants.